PENGARUH PRIVASI DAN KEAMANAN TERHADAP PENGGUNAAN MOBILE PAYMENT - Muhamad Badru Zaman; Ibrahim Bali Pamungkas; Wahyu Andri Wibowo (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
The purpose of this study was to determine how much positive and significant influence privacy and security partially or simultaneously on the performance of using mobile payment (Go-Pay). The object of this research is the students of Pamulang University Faculty of Economics and Business Management Study Program Level 1 users of mobile payment (Go-Pay). The type of research used in this research is descriptive quantitative. Methods of data collection using observation and questionnaires. The sampling technique used slovin with a number of respondents as many as 91 users. The validity of the data in this study used Validity Test, Reliability Test, and Classical Assumption Test. The result of this study is that there is a positive and significant influence partially or simultaneously between privacy and security on the use of mobile payment (Go-Pay).